The evolution of pronunciation teaching and research 25 years of intelligibility, comprehensibility, and accentedness - Levis, John (John M.); Derwing, Tracey M.; Munro, Murray J. (Benjamins current topics,, 2022)
"Inspired by Murray Munro and Tracey Derwing's 1995 seminal study of intelligibility, comprehensibility, and accentedness, this book revisits the insights of their original research and presents subsequent studies extending this work to new ways of understanding second language speech. By rejecting the nativeness approach upon which previous pronunciation research and teaching were built, Munro and Derwing's paper became the catalyst for a new paradigm of pronunciation and speech research and teaching. For the first time, pronunciation researchers had an empirically-motivated set of dimensions for assessing L2 speech. Results of many subsequent studies showed that the original insights of three partially-independent measures are indispensable to language teaching, language assessment, social evaluations of speech, and pedagogical priorities. This monograph offers 9 diverse chapters by leading researchers, all of which focus on intelligibility and or comprehensibility. This volume is essential reading for anyone interested in up-to-date coverage of L2 pronunciation matters. Originally published as special issue of Journal of Second Language Pronunciation 6:3 (2020)"--